แนวทางการบริหารงานห้องสมุดมีชีวิตของโรงเรียนศรีจอมทอง จังหวัดเชียงใหม่ - วิทยา อนุเกรียงไกร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study has two purposes ; First, to study the condition and the problems of living library administration of Sri Chom Thong School, Chiang Mai Province. Second, in order to provide guidelines for living library administration of Sri Chom Thong School, Chiang Mai Province. There are three steps; First, study the condition and the problems of living library administration of Sri Chom Thong School, Chiang Mai Province. The population in study case were a school principal and teachers of Sri Chom Thong School, Chiang Mai Province 2014. The equipment in the study case was a questionnaire. The data were analyzed by using average percent, mean and standard deviation. Second step, provide guidelines for living library administration of Sri Chom Thong School, Chiang Mai Province. Five librarians who got reward in practice from Chiang Mai Primary Educational Service Area Office from area 1–6 were selected. The equipment used in the study was a questionnaire. The data were analyzed by summarizing. The last step, inspect the efficacy of guidelines for living library administration of Sri Chom Thong School, Chiang Mai Province. A total of five people between supervisors and librarians who have much experience in library administration at least five years inspect the feasibility, the suitability and the utility for the guidelines which had been provided. The data were analyzed by using mean and standard deviation. The result of the study found that the services of the library lacking computer for searching data and lacking modern information tools. Also, the library system wasn’t up–to–date. The guidelines for living library administration of Sri Chom Thong School is PDCA (Plan–Do–Check-Act); preparation of personal and planning library framework comply with school’s policy and expenditure. Also provide responsible person for the library’s activities who work together with the librarian. Follow the plans by promoting a project of the use of library and provide the performance calendar. Prepared a questionnaire for the user in order to reorganize the efficiency of the library. The result of the feasibility, the suitability and the utility of living library administration of Sri Chom Thong School was mostly in good level.